Association between the C-reactive protein to albumin ratio with asthma and mortality in adult: a population-based study - Jun You; Yiwen He; Min Xu; Min Qian (Scientific Reports, 2024)
Abstract Asthma is a prevalent chronic disease characterized by airflow obstruction, causing breathing difficulties and wheezing. This study investigates the association between the C-reactive protein to albumin ratio (CAR) and asthma prevalence, as well as all-cause and respiratory mortality among asthma patients, using data from the 2001–2018 National Health and Nutrition Examination Survey. We included participants aged 20 years and older with complete CAR data, excluding those who were pregnant or lost to follow-up. The analysis employed weighted logistic regression and Cox proportional hazards models with stepwise adjustment, restricted cubic spline analysis for nonlinear relationships, and time-dependent ROC curves for predictive accuracy. Results showed that the highest CAR quartile significantly increased the risk of asthma (OR 1.56, 95% CI 1.38–1.78), all-cause mortality (HR 2.20, 95% CI 1.67–2.89), and respiratory mortality (HR 2.56, 95% CI 1.30–5.38). The impact of CAR on all-cause mortality was particularly significant in hypertensive patients. These findings highlight CAR’s potential as a valuable biomarker for predicting asthma prevalence and mortality, underscoring its role in asthma management and prognostication.